Analisis Kesalahan Fonologi dan Morfologi Pada Berita Kabar Priangan (Gaya Hidup) Edisi September-Oktober 2024 - De San San Nurhayati; Jelita Maulida Nurhamidah; Hesti Nurlinda; Ai Siti Nurjamilah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to analyze phonological and morphological errors in lifestyle column articles of the Kabar Priangan newspaper, September-October 2024 edition. Using a descriptive qualitative approach, this research identifies and classifies the language errors found. Data is collected through observation and note-taking techniques, where the researcher records every phonological and morphological error that appears in the text. The analysis results show various types of errors, including phoneme omission, phoneme addition, phoneme sound changes, affix usage errors, word compounding, and unnecessary word repetition. This study provides insights into the causes of errors and their impact on reader comprehension, as well as offers recommendations for improving language use in online media.